2015
DOI: 10.1186/s12913-015-1212-6
|View full text |Cite
|
Sign up to set email alerts
|

Is exposure in vivo cost-effective for chronic low back pain? A trial-based economic evaluation

Abstract: BackgroundBack pain is one of the most expensive health complaints. Comparing the economic aspects of back pain interventions may therefore contribute to a more efficient use of available resources. This study reports on a long-term cost-effectiveness analysis (CEA) and cost-utility analysis (CUA) of two treatments as viewed from a societal perspective: 1) exposure in vivo treatment (EXP), a recently developed cognitive behavioral treatment for patients with chronic low back pain who have elevated pain-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 39 publications
(46 reference statements)
0
56
0
2
Order By: Relevance
“…Various RCTs evaluated the cost-effectiveness of group cognitive behavioral approaches for chronic low back pain, with estimates of additional cost per QALY ranging from £1,786 to $7,197 (Linton and Nordin, 2006 ; Lamb et al, 2010 ; Norton et al, 2015 ). An integrated care program for sick-listed back pain patients based on a workplace intervention and graded activity was found to provide work-related economic savings in the amount of £5744 (Lambeek et al, 2010 ), but graded activity was found to be less cost-effective than exposure in vivo in another trial (Goossens et al, 2015 ). Non-significant effects were found for a CBT program added to inpatient rehabilitation for chronic low back pain (Schweikert et al, 2006 ).…”
Section: The Economic Utility Of Clinical Psychology For Pain Treatmementioning
confidence: 99%
“…Various RCTs evaluated the cost-effectiveness of group cognitive behavioral approaches for chronic low back pain, with estimates of additional cost per QALY ranging from £1,786 to $7,197 (Linton and Nordin, 2006 ; Lamb et al, 2010 ; Norton et al, 2015 ). An integrated care program for sick-listed back pain patients based on a workplace intervention and graded activity was found to provide work-related economic savings in the amount of £5744 (Lambeek et al, 2010 ), but graded activity was found to be less cost-effective than exposure in vivo in another trial (Goossens et al, 2015 ). Non-significant effects were found for a CBT program added to inpatient rehabilitation for chronic low back pain (Schweikert et al, 2006 ).…”
Section: The Economic Utility Of Clinical Psychology For Pain Treatmementioning
confidence: 99%
“…In CRPS-I, no other studies on the cost-effectiveness of rehabilitation are available. The cost-effectiveness of EXP was previously evaluated in a study comparing EXP with graded activity (GA) for individuals with low back pain (29). EXP was the preferred treatment regarding societal costs, but less convincing than in the current study, possibly because the contrast between EXP and GA, two biopsychosocial interventions, is less pronounced than between EXP and PPT, which has a biomedical focus.…”
Section: Discussionmentioning
confidence: 64%
“…Taking into account that chronic pain is often treated in multidisciplinary (inpatient) settings with restricted schedules, rapid responses seem highly relevant. 36,64 Higher levels of pain anxiety and lower levels of pain catastrophizing in our healthy sample were predicted fewer trials needed, independently of the instruction type. Considering this finding in a broader context with regard to findings from clinical samples, this may appear contradictory at first glance: while higher pain anxiety was associated with fewer trials needed, higher pain catastrophizing was related to more trials needed.…”
Section: Dovepressmentioning
confidence: 77%